2018
DOI: 10.1093/carcin/bgy102
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of hsa-miR-191/425 locus promotes breast cancer proliferation and metastasis by targeting DICER1

Abstract: The dysregulation of miRNAs is a crucial characteristic of human cancers. Herein, we observed frequent amplification of the MIR191/425 locus in breast cancer, which is correlated with poor survival outcome. We demonstrated that the miR-191/425 cluster binds the 3'UTR of the DICER1 transcript and post-transcriptionally represses DICER1 expression, thereby impairing global microRNAs biogenesis. Functionally, the forced expression of miR-191 or miR-425 stimulated the proliferation, survival, migration and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 47 publications
1
24
1
1
Order By: Relevance
“…Previous studies have reported that several genes are directly targeted by miR-191 in human cancers including TET1, TIMP3, SATB1, and DIECR1 [2729]. However, we did not detect significant changes in the expression levels of these mRNAs in Huh 7 cells transfected with a miR-191 mimic or in SMMC-7721 cells transfected with a miR-191 siRNA.…”
Section: Resultscontrasting
confidence: 88%
“…Previous studies have reported that several genes are directly targeted by miR-191 in human cancers including TET1, TIMP3, SATB1, and DIECR1 [2729]. However, we did not detect significant changes in the expression levels of these mRNAs in Huh 7 cells transfected with a miR-191 mimic or in SMMC-7721 cells transfected with a miR-191 siRNA.…”
Section: Resultscontrasting
confidence: 88%
“…MiR-191 dysregulation in different cancers, such as in hepatocellular carcinoma 34 , breast cancer 7 , pancreatic cancer 35 , gastric cancer 10 , different human cell lines of colorectal cancer 36 , and OSCC 13 , has increasingly been detected, which is in agreement with the overexpression of miR-191 in OSCC cases in this study. However, downregulation of miR-191 in follicular adenoma, anaplastic thyroid carcinoma, and papillary thyroid carcinoma 37 and downregulation of miR-191-5p in the renal cell carcinoma cell lines ACHN and 786-O 38 were in conflict with the results of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, any change in miRNA expression level may have a link to various diseases like cancer. A number of miRNAs function as both tumor suppressors and as oncogenes (oncomiR) 4 , 5 , having been shown to be involved in various cancers including breast cancer 6 - 8 , gastric cancer 9 - 11 , and OSCC 12 - 14 . Contradictory results have been reported about the miRNA expression profiles of OSCC in human societies, and extensive research needs to be conducted before clinical use 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Through mouse and human cell experiments, Ma et al demonstrated that miR-10b is highly expressed in metastatic BC cells and can mediate cell migration in the process of forward transfer and invasion [ 15 ]. In addition, Zhang et al revealed that the miR-191/425 cluster promotes the growth, invasion, and metastasis of breast tumours in vivo [ 16 ]. These results indicated that miRNAs play an important role in the development of BC.…”
Section: Discussionmentioning
confidence: 99%